Computer games: implementation into teaching and learning - Ahmad, Ibrahim; Jaafar, Azizah (Elsevier Ltd, 2012)
It is well known that a computer game other than video games is a current trend among the younger generation. Studies have shown that the use of computer games not only played by children as young as two years even up to adulthood. Integration and implementation of computer games into the classroom is also seen to help students learn with more fun and effective. The purpose of this paper is to discuss the principles of learning to be embedded in a computer game-based learning as well as aspects that can be considered when designing a computer game that will be used as the application of teaching and student learning.